ISO 14001 standard: Benefits, motivations and difficulties throughout the implementation process - Cunha, A. (2020)
Purpose The purpose of this paper is to present a summary of the benefits, motivations and difficulties in implementing the ISO 14001 standard, which is the key reference in the field of corporate environmental management. Design/methodology/approach- A literature research was carried out in order to get understanding about the key concepts of ISO 14001, to investigate the reason why companies feel motivated to adopt this EMS and to identify the associated benefits and difficulties in the implementation. Findings This paper shows the benefits found by certified companies can be classified in internal, external and relations benefits. The impact of the certification on financial and organizational performances showed to be positive. Enhancement of internal processes, strengthening of results, prevention of potential problems and a larger number of stakeholders are pointed as important performance improvements. Originality/value - This paper focuses on the ISO 14001 certification motivation and importance. Thus, this paper contribution lies on providing information regarding possible benefits and difficulties that may occur due to EMS implementation.